Characterization of T-Even Bacteriophage Substructures: I. Tail Fibers and Tail Tubes - Cummings, Donald J. (1970)
T-even bacteriophages were grown and purified in bulk quantities. The protein coats were disrupted into their component substructures by treatment with 67% dimethyl sulfoxide (DMSO). Tail fibers and tubes were purified on glycerol-CsCl-D(2)O gradients and examined with respect to sedimentation properties, subunit molecular weights, amino acid composition, isoelectric points, and morphology. It was found that intact tail fibers had a sedimentation coefficient of 12 to 13S and that dissociated fibers consisted of three classes of proteins having molecular weights of 150 K ± 10, 42 K ± 4, and 28 K ± 3 daltons. A model was constructed in which the 150-K subunit folded back on itself twice to give a three-stranded rope. Each 150-K subunit then represented a half-fiber and it was proposed that the role of the 42- and 28-K subunits was to hold each half-fiber together as well as serve as a possible link with other substructures. Isoelectric point studies also indicated that there were three different proteins with pI values of 3.5, 5.7, and 8.0. Amino acid analyses indicated that fibers had a composition distinct from other phage substructures. In addition, a striking difference was noted in the content of tryptophan among the phages examined. T4B had three to five times more tryptophan than did T2L, T2H, T4D, and T6. Intact tail tubes had an S(20,w) of 31 to 38S and dissociated tubes consisted of three proteins of molecular weights 57 K ± 5, 38 K ± 4, and 25 K ± 3 daltons. Based on degradation studies with DMSO, it was proposed that these three proteins were arranged in a helical array yielding the tube structure. Isoelectric point studies indicated that there were three major proteins in the tube whose pI values were 5.1, 5.7, and 8.5. No significant differences were observed in the amino acid content of tubes obtained from all the T-even bacteriophages.